Digital microfluidics for nucleic acid amplification - Coelho, Beatriz (2017)
This work was funded by FEDER funds through the COMPETE 2020 Program (POCI-01-0145-FEDER-007728). BV thanks SFRH/BPD/124311/2016. PVB thanksWater JPI Proj TRACE (Ref 281715).